The Ecology of Black Fly Parasites - D. P. Molloy (Black Flies: Ecology, Population Management, and Annotated World List, 1987)
The parasites of Simuliidae and their ecology are discussed in the following framework: (1) Aspects of the host-parasite system (approaches to invading the host; commencement of infection; maintenance of stability of parasitic and black fly populations; host specificity, including a table summarizing ranges of mermithid, fungal, protozoal and viral parasites among simuliid genera); (2) Physiological host-parasite interactions (location of infection within or on simuliid hosts, with a table listing this for protozoal, fungal, viral and mite parasites; effects on the black fly by the parasite, also summarized in a table; effect of the black fly on the parasite); (3) Dispersal of parasites; (4) Alternate hosts; and (5) Conclusions.
Keywords: biology